PENJADWALAN FLOWSHOP MENGGUNAKAN ALGORITMA NAWAZ ENSCORE HAM - Masudin, Ilyas; Utama, Dana Marsetya; Susastro, Febrianto (Jurnal Ilmiah Teknik Industri, 2014)
This article attempts to schedule flow shop production using Nawaz Enscore Ham (NEH) to schedule jobs machining. The objective of this paper is to minimize total makespan which could reduce total production costs. This paper is based on the case study where NEH is applied in scheduling jobs in machines and then compared with the existing machine?s scheduling. The algorithm of NEH is also used to reduce idle time of machines so that the utility or performances of the machine are maintained.  The results of NEH simulation indicate that by applying NEH algorithm to scheduling machines for 10 jobs and 5 machines can reduce 2.5 per cent or 118 minutes of completing time of jobs. It also decreases total idle time of machines about 582 minutes compared with the existing scheduling.